The Influence of Actual and Ideal Self-Congruity on Consumers’ Purchase Intentions - Tooray, Jenasha; Oodith, Devina (Journal of Economics and Behavioral Studies, 2017)
During the course of consumer behaviour research an augmented focus pertaining to consumer brand selection and the reason/s why consumers purchase a particular brand became evident. Research postulates that consumers tend to purchase brands that have personality attributes that closely correspond to their actual self-concept and enhance their self-image, thereby bringing them closer to their ideal self-concept. Self-congruity is of paramount importance to marketing for the reason that most of the products consumers purchase are influenced by the images consumers have about themselves. According to Sirgy in 1982, self-congruity defines the procedure in which consumers match their own self-concept with the imageries of a particular brand (as cited in Sohn & Yuan, 2011). In this era of hyper competition in the marketplace, it is imperative that marketers establish and preserve an enduring, mutually beneficial relationship between their brands and their target markets in order for their companies’ growth and survival. This article aims to assess the influence that actual and ideal self-congruity have on consumers’ purchase intentions with reference to the clothing and mobile phone brands that are purchased by consumers. This study was undertaken in EThekwini (Durban), South Africa and was conducted within a Public Tertiary Institution comprising of postgraduate and undergraduate students from three colleges. The institution comprised of thirteen Schools which participated in this study. A sample of 385 respondents was drawn using simple random sampling with a 100% response rate from respondents. Since students represent a lucrative market segment for marketing managers to penetrate, a survey was undertaken in order to unearth whether there exists a congruous relationship between the self-concept of students and the personality attributes of the brands they purchase; and to determine the impact that this relationship has regarding students’ brand preference, customer-brand satisfaction and brand loyalty on students’ purchase intentions. Data for the sample was collected using a self-developed, precoded questionnaire whose psychometric properties were statistically determined. Data was analyzed using descriptive and inferential statistics. The results indicate that actual and ideal self-congruity does influence purchase intentions significantly and there exists a positive relationship among students’ actual and ideal self-congruity, brand preference, customer-brand satisfaction and brand loyalty. Consumers tend to base brand choices for clothing and mobile phones very closely to their perceptions of their actual and ideal self-concepts thus this becomes important for marketers to monitor and target in order to better influence future purchase intentions of these consumers. Based on the results of the study recommendations have been made to better understand consumers and their actual and ideal selves more critically with a view to servicing them more efficiently. The results, thus enable marketing managers to improve brand loyalty, brand preference and customer-brand satisfaction among consumers; and gain insight into consumers’ actual and ideal self-congruity.